Norma Vally's kitchen fix-ups more than 30 projects for every skill level - Vally, Norma (Hoboken, N.J Wiley Pub, 2009)
From the Publisher: The DIY trend for women involves more than knitting and sewing: today more women are tending to their homes, and they're not just sewing curtains and arranging flowers. They're installing new toilets, laying ceramic floors in the kitchen, and dry walling the den. With 23 percent of all power tool purchases in 2004 made by women, and the number of unmarried females owning homes climbing by nearly 4 million owners from 1994 to 2002, when it comes to home repair, maintenance, and improvement, these sisters are doing it for themselves. At the same time, a survey by Home Depot found that 73 percent of women would like to learn more about tackling home improvements. But who has the brains, brawn, and beauty to really understand a woman's perspective and give her the confidence to conquer what had traditionally been men's territory? Norma Vally. Norma Vally is a rare combination: construction worker, former model, television and radio host. As the host of Discovery Home's Toolbelt Diva, Norma showed women how to throw out the Honey Do lists and "Honey, do it yourself." She's beautiful, sassy, confident, and competent, and with a radio show, a line of tools, a website, and her top-rated TV show she is a franchise dedicated to educating women on home repair, maintenance, and improvement. The Norma Vally book series is as sassy as Norma, packed with real-world tips showing women how to take charge of their homes. This four-color, fully illustrated series provides a basic overview of big-picture renovation. In Norma Vally's Kitchen Fix-Ups, Norma guides the reader through determining not only how to do the work, but how to determine what is right for her: How does she use her kitchen? What features are truly important? Is it the domain of one person or the family hangout? Are there storage considerations? Is plumbing position and function optimal? Then she provides an overview of the jobs best left to professionals and those the reader can master with Norma's guidance: fixing a leaky faucet, installing a backsplash, building in recessed lighting, resurfacing countertops. Tasks are broken down into three levels of difficulty and cover sinks, countertops, appliances, cabinets, walls, and floors. The book is written in Norma's trademark can-do, sassy voice and provides confidence to the most nervous renovator, showing readers that Honey-Do lists can truly become a thing of the past. The book is packaged with a $9.99 value-add DVD of Norma walking the user through three key tasks, one at each level of difficulty: cleaning out a faucet aerator, repairing a leaky faucet, and installing a new faucet. None of the competition contains this multimedia element
Express Facelift -- 1: Sinks -- Faucet aerator maintenance -- Tighten a loose faucet -- Unclog a drain -- Fix a sprayer -- 2: Countertops -- Restore a solid-surface countertop -- Replace a cracked tile -- 3: Appliances -- Dishwasher maintenance -- Refrigerator maintenance -- Stove maintenance -- 4: Cabinets -- Add or replace knobs and pulls -- Restore wood cabinet finish -- 5: Walls And Floors -- Patch holes in drywall -- Repair torn vinyl flooring -- Reseal a damaged wood floor section -- Corrective Treatment -- 6: Sinks -- Repair a leaky faucet -- Snake a stubborn sink clog -- 7: Countertops -- Resurface a laminate countertop -- Tile a backsplash -- 8: Appliances -- Repair a garbage disposal -- Repair an icemaker -- 9: Cabinets -- Refinish wood cabinets -- 10: Walls And Floors -- Install a task light fixture -- Refinish wood floors -- Intensive Treatment -- 11: Sinks -- Install a new faucet -- Replace a shut-off valve -- Install an under-sink water filtration system -- Install a new drop-in sink -- 12: Countertops -- Install a laminate countertop -- Tile a countertop -- 13: Appliances -- Install a dishwasher -- Install a microwave/exhaust fan -- 14: Cabinets -- Install new cabinets -- 15: Walls And Floors -- Install a floating floor -- Tile a floor -- Install recessed lights -- Total Indulgence -- 16: Footprint And Layout: What Works For You -- Exploring the possibilities -- Creating storage space -- Wheelchair-accessible kitchen -- 17: Design: Creating The Ideal Look And Feel For Your Kitchen -- Where to get started -- Flooring -- Walls -- Cabinetry -- Countertops -- Appliances, sinks, and faucets -- Lighting -- Index
Includes index
System requirements: PC running Windows 98 (or later), Macintosh running Mac OS X; DVD-ROM drive
1
Keywords: Do-it-yourself work; Kitchens -- Maintenance and repair -- Amateurs' manuals; Kitchens -- Remodeling -- Amateurs' manuals; Women construction workers